2013
DOI: 10.1016/j.brainres.2012.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Differential seizure response in two models of cortical heterotopia

Abstract: Malformations of cortical development (MCD) are linked to epilepsy in humans. MCD encompass a broad spectrum of malformations, which occur as the principal pathology or a secondary disruption. Recently, Rosen et al. (2012) reported that BXD29-Trl4lps-2J/J mice have subcortical nodular heterotopias with partial agenesis of the corpus callosum (p-ACC). Additionally Ramos and colleagues (2008) demonstrated that C57BL/10J mice exhibit cortical heterotopias with no additional cortical abnormalities. We examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(49 reference statements)
1
7
1
Order By: Relevance
“…Heterotopia in control and experimentally-treated mice may affect performance on the task(s) tested or interact with treatment regimes. This assertion is supported by previous findings that mice with MLH exhibit deficits in learning, memory [2830,32], and sensory discrimination tasks [33,34,36] as well as neocortical hyperexcitability based on response to chemi-convulsant treatment [38,49]. Finally, the extent to which gene/protein expression changes are observed in neurons and glia in heterotopia remains unknown; these changes could affect neocortical expression studies, particularly when the presence/absence of heterotopia is not known prior to tissue harvesting.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Heterotopia in control and experimentally-treated mice may affect performance on the task(s) tested or interact with treatment regimes. This assertion is supported by previous findings that mice with MLH exhibit deficits in learning, memory [2830,32], and sensory discrimination tasks [33,34,36] as well as neocortical hyperexcitability based on response to chemi-convulsant treatment [38,49]. Finally, the extent to which gene/protein expression changes are observed in neurons and glia in heterotopia remains unknown; these changes could affect neocortical expression studies, particularly when the presence/absence of heterotopia is not known prior to tissue harvesting.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, mice with heterotopia exhibit impaired learning of spatial and non-spatial memory tasks [2832] and deficits in sensory discrimination tasks [3336], consistent with cognitive deficits associated with MLH. Furthermore, mice with MLH have lower seizure thresholds and shorter latency to seizures following chemi-convulsant treatment [37,38], which mimic brain excitability changes observed in epileptics with MLH. Thus, behavioral changes in mice with MLH closely resemble those observed in humans with MLH, demonstrating the utility of mice as a model of human MLH.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data indicate that there exists a diverse complement of neurons in MLH and suggest that these neurons may participate in a synaptic network that contributes to the cortical dysfunction manifested by patients with MLH. Consistent with this hypothesis, mice with MLH have impaired learning of spatial and nonspatial memory tasks [24,25,26,27,28], sensory processing deficits [29,30,31,32] and increased seizure susceptibility [34]. Future studies should be aimed at characterizing the synaptic circuitry and physiological profile of neurons in C57BL/6J mice with MLH, toward gaining a better understanding of how heterotopia cause cortical dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, findings in mice with MLH mimic the cognitive defects seen in humans with MLH. Furthermore, we have shown that mice with MLH also have lower seizure thresholds and shorter latency to seizures following chemi-convulsant treatment [33,34], which mimic the brain excitability changes observed in epileptic humans with MLH. Thus, behavioral changes in mice with MLH closely resemble those observed in humans with MLH, demonstrating the utility of mice as a model of human MLH.…”
Section: Introductionmentioning
confidence: 99%
“…Other models were only reported to exhibit increased susceptibility to convulsant-evoked seizures: pilocarpine-induced seizures in Heco mice [51] and RA-GEF-1 conditional KO [111]. Surprisingly, BXD29-Trl4lps 2J/J mice were found more resistant to PTZ-induced seizures than wild-type controls [112]. Seizure susceptibility was not investigated in RhoA conditional KO.…”
Section: Spontaneous and Induced Seizures In Sbh Modelsmentioning
confidence: 99%